Respuesta :

Answer:

x = 1

Step-by-step explanation:

Simplifying

7(x + 1) + -2 = 5(x + 1) + 2

Reorder the terms:

7(1 + x) + -2 = 5(x + 1) + 2

(1 * 7 + x * 7) + -2 = 5(x + 1) + 2

(7 + 7x) + -2 = 5(x + 1) + 2

Reorder the terms:

7 + -2 + 7x = 5(x + 1) + 2

Combine like terms: 7 + -2 = 5

5 + 7x = 5(x + 1) + 2

Reorder the terms:

5 + 7x = 5(1 + x) + 2

5 + 7x = (1 * 5 + x * 5) + 2

5 + 7x = (5 + 5x) + 2

Reorder the terms:

5 + 7x = 5 + 2 + 5x

Combine like terms: 5 + 2 = 7

5 + 7x = 7 + 5x

Solving

5 + 7x = 7 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.

5 + 7x + -5x = 7 + 5x + -5x

Combine like terms: 7x + -5x = 2x

5 + 2x = 7 + 5x + -5x

Combine like terms: 5x + -5x = 0

5 + 2x = 7 + 0

5 + 2x = 7

Add '-5' to each side of the equation.

5 + -5 + 2x = 7 + -5

Combine like terms: 5 + -5 = 0

0 + 2x = 7 + -5

2x = 7 + -5

Combine like terms: 7 + -5 = 2

2x = 2

Divide each side by '2'.

x = 1

Simplifying

x = 1

Answer:

Hello! The answer is x = 1.

Step-by-step explanation:

To solve this equation, we need to find x.

The first step in approaching this problem would be to use the distributive property:

7(x + 1) - 2 = 5(x + 1) + 2 will turn into:

7x + 7 - 2 = 5x + 5 + 2

Now, you can combine like terms on each side of the equation:

7x + 5 = 5x + 7

Now, you want to get the x's on one side and the whole numbers on the other side. In order to do this, we will subtract 5 from both sides and subtract 5x from both sides:

7x + 5 = 5x + 7

-5x -5   -5x  -5

This will leave us with:

2x = 2

We will have to now divide both sides by 2 to get x by itself:

2x = 2

--     --

2     2

This leaves us with the result: x = 1